Camel Reaiung in the Indian Arid Zone - Khanna, N D; Rai, A K (Annals of Arid Zone, 2016)
With about 6.3% of the world camel population, India ranks third after Somalia and Sudan in this respect. According to the Livestock Census(1982), Rajasthan State alone accounted for 70% of India’s total camel population of which 84.5% was found in its II western arid districts. The Camel density in these II districts was 3.06 per sq km and 4.78 per 100 persons, contributing 9.9% towards the total domestic herbivore livestock. The augmentation of camel rearing has a strong case in the Indian arid zone. The camel has great adaptive mechanisms and is well suited for life in the desert. The major camel resources are energetics, milk, meat, hair and hide. It is necessary that untapped potentials of camels are explored scientifically to make camel rearing as economically viable proposition in terms of the social and agrostological aspects of livestock management and for providing sustainable subsistence to the people inhabiting Indian arid region.